Comparative Study on the Phytochemical Composition and Antioxidant Activity of Grecian Juniper (Juniperus excelsa M. Bieb) Unripe and Ripe Galbuli - Stankov, Stanko (Plants (Basel), 2020)
Grecian juniper (Juniperus excelsa M. Bieb.) is an evergreen tree and a rare plant found in very few locations in southern Bulgaria. The aim of this study was to evaluate the phytochemical content and antioxidant potential of J. excelsa unripe and ripe galbuli from three different locations in Bulgaria. The essential oil content ranged between 1.9% and 5.1%, while the lipid fraction yield was between 4.5% and 9.1%. The content of total chlorophyll was 185.4–273.4 μg/g dw. The total carotenoid content ranged between 41.7 and 50.4 μg/g dw of ripe galbuli, and protein content was between 13.6% and 16.4%. Histidine (5.5 and 8.0 mg/g content range) and lysine (4.0 and 6.1 mg/g) were the major essential amino acids. The antioxidant potential of the 95% and 70% ethanol extracts was analyzed using four different methods. A positive correlation between the antioxidant potential and phenolic content of the galbuli was found. The results obtained in this study demonstrated the differences in phytochemical composition and antioxidant capacity of J. excelsa galbuli as a function of maturity stage and collection locality.